Effect of thymol and Pickering stabilization on in-vitro digestion fate and oxidation stability of plant-derived flaxseed oil emulsions. (1st May 2020) - Nikbakht Nasrabadi, Maryam; Sedaghat Doost, Ali; Goli, Sayed Amir Hossein; Van der Meeren, Paul
Highlights: Plant-based Pickering stabilized flaxseed oil (FO) emulsions containing thymol were made. The plant-derived particles consisted of flaxseed protein and polysaccharide. Thymol was an effective natural antioxidant. FO oxidation and digestion were slowed down after incorporation in Pickering emulsions. Abstract: The aim of this study was to evaluate the effect of Pickering stabilization by biopolymer-based particles (bioparticles), consisting of flaxseed protein and polysaccharides, and of the addition of thymol to the oil phase on the oxidation stability, and digestion fate of flaxseed oil (FO) emulsions, compared to bulk FO and conventional emulsions stabilized by polysorbate 80 (PS80). Applying Pickering stabilization and thymol simultaneously was a successful approach to retard FO oxidation. Moreover, lipid digestion was slower in bioparticle-stabilized emulsions compared to PS80 stabilized emulsions. The thymol bioaccessibility increased after incorporation into FO Pickering emulsions in comparison to the bulk oil. The results suggested that the combination of Pickering stabilization and thymol addition to the oil phase can be used as a promising way of protecting highly unsaturated oils such as FO against oxidation. These emulsions are also applicable for designing functional foods with controlled lipid digestion.